Cerebral oximetry and return of spontaneous circulation after cardiac arrest: A systematic review and meta-analysis. (September 2015) - Sanfilippo, Filippo; Serena, Giovanni; Corredor, Carlos; Benedetto, Umberto; Maybauer, Marc O.; Al-Subaie, Nawaf; Madden, Brendan; Oddo, Mauro; Cecconi, Maurizio
Abstract: Aim: The prediction of return of spontaneous circulation (ROSC) during resuscitation of patients suffering of cardiac arrest (CA) is particularly challenging. Regional cerebral oxygen saturation (rSO2 ) monitoring through near-infrared spectrometry is feasible during CA and could provide guidance during resuscitation. Methods: We conducted a systematic review and meta-analysis on the value of rSO2 in predicting ROSC both after in-hospital (IH) or out-of-hospital (OH) CA. Our search included MEDLINE (PubMed) and EMBASE, from inception until April 4th, 2015. We included studies reporting values of rSO2 at the beginning of and/or during resuscitation, according to the achievement of ROSC. Results: A total of nine studies with 315 patients (119 achieving ROSC, 37.7%) were included in the meta-analysis. The majority of those patients had an OHCA ( n  = 225, 71.5%; IHCA: n  = 90, 28.5%). There was a significant association between higher values of rSO2 and ROSC, both in the overall calculation (standardized mean difference, SMD –1.03; 95%CI –1.39, –0.67; p  < 0.001), and in the subgroups analyses (rSO2 at the beginning of resuscitation: SMD –0.79; 95%CI –1.29, –0.30; p  = 0.002; averaged rSO2 value during resuscitation: SMD –1.28; 95%CI –1.74, –0.83; p  < 0.001). Conclusions: Higher initial and average regional cerebral oxygen saturation values are both associated with greater chances of achieving ROSC in patients suffering of CA. A note of caution should be made in interpreting these results due to the small number of patients and the heterogeneity in study design: larger studies are needed to clinically validate cut-offs for guiding cardiopulmonary resuscitation.